MANUSIA DAN PENDIDIKAN DALAM PERSPEKTIF AL-ATTAS - Baharuddin AbdRahman (DIRASAT: Jurnal Studi Islam dan Peradaban, 2018)
This research is a type of library research, trying to explain al-Attas’ conception of man and education. The results of the study found that: (1) man is not a creature that evolved from animals, and therefore "al-ḥayawān" in the definition of man as: al-ḥayawān al-nāṭiq cannot be translated as “animals,” but a “living being”, so man, if it is constructed, is defined as a living being who is rational or who can speak (i.e., a living being that speaks); (2) the nature of man consists of two dimensions: body and soul (3) ‘ilm farḍ‘ ain is a nutrient for the dimensions of man’s soul, while ‘ilm farḍ kifāyah is nutrition for the dimensions of the body. These two types of knowledge are like boats by which man can achieve educational goals while at the same time delivering the goals and functions of his life (i.e., ‘ibādullah and khalīfatullāh) on earth.